Acute necrotizing ulcerative gingivitis associated with Stenotrophomonas Maltophilia, a case report - Souza, Mayara Larissa Moura de; Castelo-Branco, Isabela Vicência Menezes; Holanda, Laís Azevedo Lins de; Frade, Angelica Lopes; Santos, Cristianne de Barros; Moura, Virgínia Costa; Taguchi, Leila Coutinho; Vida, Aurora Karla de Lacerda (Journal of Oral Diagnosis, 2020)
The aim of this study was to report a case of Acute Necrotizing Ulcerative Gingivitis (ANUG) related to chemotherapy toxicity and infection by Stenotrophomonas maltophilia bacterium, until then only one case of ANUG associated with this bacterium has been described in the literature. Female patient, 20 years old, diagnosed with poorly differentiated neuroendocrine carcinoma, undetermined primary site, was treated with etoposide and cisplatin. She presented halitosis, desquamative necrotic gingival tissue, with pseudomembrane formation compatible with ANUG related to chemotherapy toxicity and infection by Stenotrophomonas maltophilia bacterium. The Standard Operational Protocol for Oral Care (Oral SOP) adapted by VIDAL, AKL (2012), with topical application of oral sodium bicarbonate solution, 0.12% chlorhexidine digluconate, and hydrogen peroxide 10 volumes diluted with water, presenting tissue recovery. Early diagnosis and appropriate treatment with a multiprofessional team are decisive measures in the prognosis of pathogen infection and in the patient’s quality of life.